Weed interference and fruit yield of Chilli Pepper (Capsicum Annum) as influenced by plant density - Adenubi OO; Sanni KO (Open Journal of Plant Science - Peertechz Publications, 2020)
Plant spacing is one of the agronomic practices that influence crop growth and development. The influence of spacing on weed interference and fruit yield of Capsicum annum was evaluated at the Teaching Research farm, Lagos State Polytechnic, Ikorodu during 2019 planting season. Three treatment consisted of chilli pepper transplanted at 60cm x 60cm, 60cm x 45cm and 60cm x 35cm replicated three times in a Randomized Complete Block Design (RCBD). Parameters tested were, Weed Cover Score (WCS), Weed Density (WD), Weed Fresh Weight (WFW), Plant Height (PH), Stem Girth (SG) and number of leaves at 3, 6 and 9 (WAT), number of days to 50% flowering, number of fruits per plot and fruit yield. Result showed that, plant density significantly affected the yield of pepper. Pepper transplanted at 60cm x 45cm gave highest yield (124kg/ha-1) and moderate weed suppression, as against 60cm x 60cm and 60cm x 35cm which recorded 36.96kg/ha-1 and 32,49 kg/ha-1 respectively. It is therefore recommended that farmers in Ikorodu should adopt 60cm x 45cm for growing chilli pepper.